Making Stakeholder Theory Whole - Donaldson, Thomas (Academy of Management Review, 1999)
The article focuses on questions concerning stakeholder theory and methods of unifying the theory. It states that two methodological versions of stakeholder theory, instrumental and normative, converge, with instrumental versions relying on hypothetical claims on the best route to achieve goals, while normative versions rely more on ethical claims. It mentions that connective logic linking the two needs to be rigorous as the two methodologies are divergent in nature. The article suggests there is logic that can link normative and empirical beliefs together. It states that the means of holding together normative and instrumental segments of stakeholder theory lies inside the minds of corporate executives.